Selection of RNA aptamers targeting hypoxia in cancer - Nuzzo, Silvia; Iaboni, Margherita; Ibba, Maria Luigia; Rienzo, Anna; Musumeci, Domenica; Franzese, Monica; Roscigno, Giuseppina; Affinito, Alessandra; Petrillo, Gianluca; Quintavalle, Cristina; Ciccone, Giuseppe; Esposito, Carla Lucia; et al. (Frontiers in Molecular Biosciences, 2022)
Hypoxia plays a crucial role in tumorigenesis and drug resistance, and it is recognized as a major factor affecting patient clinical outcome. Therefore, the detection of hypoxic areas within the tumour micro-environment represents a useful way to monitor tumour growth and patients’ response to treatments, properly guiding the choice of the most suitable therapy. To date, non-invasive hypoxia imaging probes have been identified, but their applicability in vivo is strongly limited due to an inadequate resistance to the low oxygen concentration and the acidic pH of the tumour micro-environment. In this regard, nucleic acid aptamers represent very powerful tools thanks to their peculiar features, including a high stability to harsh conditions and a small size, resulting in an easy and efficient tumour penetration. Here, we describe a modified cell-SELEX (Systematic Evolution of Ligands by EXponential enrichment) approach that allows the isolation of specific RNA aptamers for the detection of the hypoxic phenotype in breast cancer (BC) cells. We demonstrated the effectiveness of the proposed method in isolating highly stable aptamers with an improved and specific binding to hypoxic cells. To our knowledge, this is the first example of a cell-SELEX approach properly designed and modified to select RNA aptamers against hypoxia-related epitopes expressed on tumour cell surface. The selected aptamers may provide new effective tools for targeting hypoxic areas within the tumour with a great clinical potential.